2008
DOI: 10.1124/mol.108.046854
|View full text |Cite
|
Sign up to set email alerts
|

17-β-Estradiol Inhibits Transforming Growth Factor-β Signaling and Function in Breast Cancer Cells via Activation of Extracellular Signal-Regulated Kinase through the G Protein-Coupled Receptor 30

Abstract: Breast cancer development and breast cancer progression involves the deregulation of growth factors leading to uncontrolled cellular proliferation, invasion and metastasis. Transforming growth factor (TGF)-beta plays a crucial role in breast cancer because it has the potential to act as either a tumor suppressor or a pro-oncogenic chemokine. A cross-communication between the TGF-beta signaling network and estrogens has been postulated, which is important for breast tumorigenesis. Here, we provide evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 38 publications
1
61
2
1
Order By: Relevance
“…Arterial rings were stretched under 2 g (aorta), 1 g (carotid artery), or 0.5 g (mesenteric and renal artery) of basal tension and allowed to equilibrate for 45 min in Krebs solution bubbled with 95% O2-5% CO2 at 37°C. These basal tensions produced maximal KCl contraction, and further increases in basal tension did not cause further contraction to KCl (72 (21,37), and the percent vascular relaxation was measured. For concentration-response curves, each ER agonist concentration was added, the vascular response was observed until it reached steady state or for 10 min, and the next concentration was then added.…”
Section: Methodsmentioning
confidence: 99%
“…Arterial rings were stretched under 2 g (aorta), 1 g (carotid artery), or 0.5 g (mesenteric and renal artery) of basal tension and allowed to equilibrate for 45 min in Krebs solution bubbled with 95% O2-5% CO2 at 37°C. These basal tensions produced maximal KCl contraction, and further increases in basal tension did not cause further contraction to KCl (72 (21,37), and the percent vascular relaxation was measured. For concentration-response curves, each ER agonist concentration was added, the vascular response was observed until it reached steady state or for 10 min, and the next concentration was then added.…”
Section: Methodsmentioning
confidence: 99%
“…ERa blocks TGFb signaling in a nongenomic manner by promoting SMAD2/3 degradation (16) and activation of MAPK through GPR30 (17). Furthermore, it has been demonstrated that SMAD3 and SMAD4 act as coactivators and corepressors, respectively, for ERainduced gene expression (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of 17-b E 2 on these tissues are either mediated through ER binding to EREs directly regulating gene expression, via ER interaction with other transcription factors or by nonnuclear actions that seem to be mediated by membrane-bound ERs (Rae & Johnson 2005, Kleuser et al 2008, Peng & Jordan 2008. Estrogens are known to stimulate proliferation of hormone-dependent tissues for example by activation of cell cycle genes (Kashima et al 2009).…”
Section: Introductionmentioning
confidence: 99%